Effect of Seashell Powder on Flexural and Compressive Strength of Cement Mortar in Early Age - Abdoullah, Namdar; Fadzil, Mat Yahaya; Chua, Pei Shan; Nabila Shahilla, Rajagopal (Trans Tech Publications, Switzerland, 2014)
The several structures have been failed due to low flexural and compressive strength of OPC paste. Many waste materials are applicable for modify flexural and compressive strength of cement mortar. Among the additives, a natural additive has been selected. The effect of seashell powder on flexural and compressive strength of cement mortar has been investigated. The result indicated that with replacement of 1% seashell, the deflection, time to failure and maximum load to failure of concrete beam has been improved. And the strain, time to failure and compressive modulus elasticity of cubic specimen has not considerably been changed. The more investigation on macro and micro property of OPC is necessary to obtain better results.